Glycine Receptor Subtypes and Their Roles in Nociception and Chronic Pain - San Martín, Victoria P.; Sazo, Anggelo; Utreras, Elías; Moraga-Cid, Gustavo; Yévenes, Gonzalo E. (Frontiers in Molecular Neuroscience, 2022)
Disruption of the inhibitory control provided by the glycinergic system is one of the major mechanisms underlying chronic pain. In line with this concept, recent studies have provided robust proof that pharmacological intervention of glycine receptors (GlyRs) restores the inhibitory function and exerts anti-nociceptive effects on preclinical models of chronic pain. A targeted regulation of the glycinergic system requires the identification of the GlyR subtypes involved in chronic pain states. Nevertheless, the roles of individual GlyR subunits in nociception and in chronic pain are yet not well defined. This review aims to provide a systematic outline on the contribution of GlyR subtypes in chronic pain mechanisms, with a particular focus on molecular pathways of spinal glycinergic dis-inhibition mediated by post-translational modifications at the receptor level. The current experimental evidence has shown that phosphorylation of synaptic α1ß and α3ß GlyRs are involved in processes of spinal glycinergic dis-inhibition triggered by chronic inflammatory pain. On the other hand, the participation of α2-containing GlyRs and of ß subunits in pain signaling have been less studied and remain undefined. Although many questions in the field are still unresolved, future progress in GlyR research may soon open new exciting avenues into understanding and controlling chronic pain.